2019
DOI: 10.1097/md.0000000000015385
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ultrasound-guided serratus plane block, in combination with general anesthesia, on intraoperative opioid consumption, emergence time, and hemodynamic stability during video-assisted thoracoscopic lobectomy

Abstract: Background: Thoracotomy is one of the most painful surgeries; therefore, video-assisted thoracoscopic surgery (VATS) was developed to reduce the surgical stress of thoracotomy. Although VATS results in reduced postoperative pain compared with thoracotomy, it is still painful. Serratus plane block (SPB) is a novel technique that provides lateral chest wall analgesia by blocking the lateral branch of the intercostal nerve. Methods: We conducted a prospective study in 50 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 39 publications
2
36
0
1
Order By: Relevance
“…. Fifty‐one studies were identified for inclusion in this review, of which nine were RCTs involving a total of 637 patients (see also Supporting Information, Table S1). Eight RCTs evaluated the serratus anterior plane block in the setting of video‐assisted thoracoscopic surgery (five studies ) and thoracotomy (three studies ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…. Fifty‐one studies were identified for inclusion in this review, of which nine were RCTs involving a total of 637 patients (see also Supporting Information, Table S1). Eight RCTs evaluated the serratus anterior plane block in the setting of video‐assisted thoracoscopic surgery (five studies ) and thoracotomy (three studies ).…”
Section: Resultsmentioning
confidence: 99%
“…Fifty‐one studies were identified for inclusion in this review, of which nine were RCTs involving a total of 637 patients (see also Supporting Information, Table S1). Eight RCTs evaluated the serratus anterior plane block in the setting of video‐assisted thoracoscopic surgery (five studies ) and thoracotomy (three studies ). Five of these compared single‐injection serratus anterior plane block with systemic analgesia alone ; one compared it with thoracic paravertebral blockade and with systemic analgesia alone ; and one compared it with PECS 2 blocks and with intercostal nerve blocks .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[17] As an important element of the multimodal analgesia program, regional block is a type of analgesia with high safety and less adverse effects. [18] We chose the subcostal approach to QLB in the study because there are several advantages of this method. (1) It can provide a higher sensory block plane due to higher needle insertion, and we can observe the extent of LA spread in the parasagittal oblique plane.…”
Section: Discussionmentioning
confidence: 99%